2003
DOI: 10.1097/00004356-200306000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of water-based exercise in patients with chronic kidney disease

Abstract: The possible beneficial effect of regular aquatic exercise on cardiorespiratory, renal lipid parameters and oxidative stress status was studied in patients with mild to moderate renal failure. The exercise group did low-intensity aerobic exercise in the pool during a period of 12 weeks, twice a week, with sessions lasting for 30 min. Matched control participants remained sedentary. The results showed that in the exercise group all cardiorespiratory functional parameters improved and resting blood pressure lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 26 publications
6
74
1
1
Order By: Relevance
“…The findings demonstrated that patients with moderate CKD randomized to receive an exercise and lifestyle intervention improved CRF, body composition, diastolic function, and preserved ventriculovascular coupling. Our results are in agreement with previous reported findings from small studies (29)(30)(31)(32)(33)(34)(35) showing that exercise training is effective in improving CRF in patients with CKD. Uremic cardiomyopathy, comprising LV dilation, hypertrophy, and impaired diastolic and systolic function, is common in late stage CKD and a strong predictor of adverse cardiovascular prognosis (8).…”
Section: Discussionsupporting
confidence: 93%
“…The findings demonstrated that patients with moderate CKD randomized to receive an exercise and lifestyle intervention improved CRF, body composition, diastolic function, and preserved ventriculovascular coupling. Our results are in agreement with previous reported findings from small studies (29)(30)(31)(32)(33)(34)(35) showing that exercise training is effective in improving CRF in patients with CKD. Uremic cardiomyopathy, comprising LV dilation, hypertrophy, and impaired diastolic and systolic function, is common in late stage CKD and a strong predictor of adverse cardiovascular prognosis (8).…”
Section: Discussionsupporting
confidence: 93%
“…It is consistent with previous study revealing that physical inactivity related to an increase risk of KD incidence (Stengel et al, 2003). In addition, a study in KD patients reported that regular water-based exercise (30 minutes, twice a week) associated with decrease of proteinuria and increase of glomerular filtration rate (Pechter et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In 17 patients with mild-to-moderate CKD, aerobic water-based exercise significantly reduced lipid peroxidation products (malondialdehyde and 4-hydroxyalkenals) and increased levels of the antioxidant glutathione compared with a sedentary control group (55). Similarly, intradialytic aerobic training for 4 months reduced thiobarbituric acid reactive substance, a product of lipid peroxidation, by 38% in hemodialysis patients compared with usual care (56).…”
Section: Osmentioning
confidence: 93%
“…In addition to eNOS activation, ET results in more efficient antioxidative defense mechanisms (e.g., by reducing ROS production [reduction in NAD(P)H expression, less eNOS uncoupling, etc.] and increasing the expression of antioxidative enzymes and ROS scavengers [e.g., glutathione]) (9,55,56). As such, ROS-mediated breakdown of NO is prevented.…”
Section: No Bioavailabilitymentioning
confidence: 99%